PERBEDAAN KEKERASAN PERMUKAAN ENAMEL SETELAH APLIKASI FLUORIDE VARNISH DAN CASEIN PHOSPO PEPTIDE-AMORPHOUS CALSIUM PHOSPHATE FLUORIDE (CPP-ACPF) (PENELITIAN IN VITRO) - Sinta Puspita; Adioro Soetojo; Sri Kunarti (Conservative Dentistry Journal, 2017)
Background: Caries is a chronic, slowly progressing disease, with symptoms not detected at the onset of the disease but generally much later. Its initiation is associated with demineralization (calcium and phosphate loss) of subsurface tooth enamel, resulting in the formation of a subsurface lesion. To restore the natural equilibrium, either remineralization must be enhanced or demineralization must be retarded. There are some topical agents that can enhance remineralization such as topical fluor and casein phosphopeptide – amorphous calcium phosphate (CPP-ACP). Purpose: The aim of this study is to analyze the differences of the enamel surface microhardness after application of fluoride varnish and CPP-ACPF. Methode: 27 blocks bovine enamel were devided into 3 groups. Group 1 – control (No surface treatment), group 2 – fluoride varnish and group 3 – CPP-ACPF. Initial surface hardness enamel was measured for all enamel specimens. Artificial enamel carious lesions were created by immersing enamel samples to demineralization solution (pH 4,5) for 72 hours at temperature 370 C. The surface microhardness of demineralized enamel specimens was measured. A caries progression test (pH cycling) was carried out, which consisted of alternative demineralization (3 hours), remineralization with artificial saliva (21 hours) and application topical agent twice a day for 14 days. Then, the last surface enamel microhardness is measured. Result: Group 3 showed significantly highest Vickers hardness number (P<0,05) followed by group 2 and the lowest is group 1. Conclusions: This study proved that enamel surface microhardness after application of CPP-ACPF was higher than fluoride varnish.